Dividend Policy: Profitability and Investment Opportunities for Public Companies - Kiki Rizky Amalia; Adita Nafisa (SEIKO : Journal of Management & Business, 2022)
Abstract This study aims to determine the effect of profitability and investment opportunities on the dividend policy of LQ45 indexed public companies on the Indonesia Stock Exchange. Profitability is assessed using the Return on Assets (ROA) and Return on Investment (ROI), investment opportunities are assessed using Capital Expenditure to Book Value Assets (CAPBV), Capital Expenditure to Market Value Assets (CAPMVA), Investment to Net Sales (IONS), and dividend policy is assessed using Dividend Payout Ratio (DPR). This research method uses descriptive quantitative research. The results of this study indicate that profitability and investment opportunities have no significant effect on dividend policy, but simultaneously profitability and investment opportunities have a significant effect on dividend policy. Kata Kunci: Dividend Policy, Profitability, Investment Opportunity